Moving Grating Technique: A New Method for the Determination of Electron and Hole Mobilities and their Lifetime - Hundhausen, Martin; Ley, Lothar; et al. (Applied Physics Letters, 1993)
A new technique to determine the mobilities and lifetime of photogenerated electrons and holes in semiconductors relies on the short circuit current that is induced perpendicularly to a moving interference grating. Theoretical expressions for the short circuit current are derived that relate the carrier mobilities and their lifetime to the velocity and spatial period of the grating. The technique has been implemented and was successfully applied to a-Si:H.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.moving